Relative effectiveness of substrate-inoculum ratio and initial pH on hydrogen production from palm oil mill effluent: Kinetics and statistical optimization - Mishra, Puranjan; Ameen, Fuad; Rubaiyi, M. Zaid; Singh, Lakhveer; Zularisam, A. W.; Islam, M. Amirul; Gupta, Arun; Al Nadhari, Saleh (Elsevier, 2019)
The present study has enabled to establish an appropriate kinetic and operational condition for hydrogen production using ultrasonicated palm oil mill effluent (POME). The kinetic analysis was performed corresponds to cumulative hydrogen (H2) production by varying substrate-inoculum ratio (COD/VS) from 0.2 to 0.6. The maximum H2 production potential (P) of 448 mL H2 with lag-time (ρ) of 8.2 h and H2 production rate (Rm) of 14.62 mL H2 h−1 was achieved using the substrate-inoculum ratio of 0.6. However, the Rm of 17.979 mL H2 h−1 with the ρ of 16.84 h, which is almost double than the substrate-inoculum ratio of 0.6 was observed at a substrate-inoculum ratio of 0.4. Furthermore, response surface methodology (RSM), including experimental design, regression analysis, was successfully applied to achieved optimum substrate-inoculum ratio and initial pH for biological H2 production from ultrasonicated POME. The maximum yield of 0.416 L H2/g-CODremoval was observed at the optimum conditions of substrate-inoculum ratio of 0.5 and an initial pH of 5.0. The linear, quadratic and interactive effect of substrate-inoculum ratio and initial pH on H2 yield were significant.